2011
DOI: 10.1073/pnas.1100023108
|View full text |Cite
|
Sign up to set email alerts
|

p31 comet promotes disassembly of the mitotic checkpoint complex in an ATP-dependent process

Abstract: Accurate segregation of chromosomes in mitosis is ensured by a surveillance mechanism called the mitotic (or spindle assembly) checkpoint. It prevents sister chromatid separation until all chromosomes are correctly attached to the mitotic spindle through their kinetochores. The checkpoint acts by inhibiting the anaphase-promoting complex/cyclosome (APC/C), a ubiquitin ligase that targets for degradation securin, an inhibitor of anaphase initiation. The activity of APC/C is inhibited by a mitotic checkpoint com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 25 publications
5
103
1
Order By: Relevance
“…We found that the hydrolysis of ATP at the β−γ position was required for both for the activation of APC/C and for the disassembly of MCC (10); this was different from the previously described requirement of checkpoint inactivation for ubiquitylation (11,12), because the latter process involves the cleavage of the α−β bond of ATP (13). We have furthermore observed that β−γ-hydrolyzable ATP is needed for the action of p31 comet (a Mad2-binding protein known to be involved in checkpoint silencing and mitotic exit) (14-16) to promote MCC dissociation (17). Surprisingly, this process caused the dissociation of Cdc20 from BubR1 in MCC, even though p31 comet binds to Mad2 in this complex (17).…”
contrasting
confidence: 42%
See 3 more Smart Citations
“…We found that the hydrolysis of ATP at the β−γ position was required for both for the activation of APC/C and for the disassembly of MCC (10); this was different from the previously described requirement of checkpoint inactivation for ubiquitylation (11,12), because the latter process involves the cleavage of the α−β bond of ATP (13). We have furthermore observed that β−γ-hydrolyzable ATP is needed for the action of p31 comet (a Mad2-binding protein known to be involved in checkpoint silencing and mitotic exit) (14-16) to promote MCC dissociation (17). Surprisingly, this process caused the dissociation of Cdc20 from BubR1 in MCC, even though p31 comet binds to Mad2 in this complex (17).…”
contrasting
confidence: 42%
“…We previously found that ATP was required for exit from mitotic checkpoint (10) and observed that ATP cooperated with the Mad2-binding protein p31 comet to promote the disassembly of MCC (17). However, the mode of the action of ATP in these processes remained unknown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…But recent attention has focused on mutual inhibition between the MCC and the APC/C (Reddy et al 2007), which requires a particular APC/C subunit, APC15 (Mansfeld et al 2011;Foster and Morgan 2012;Uzunova et al 2012). In animal cells, a second important player for MCC disassembly is the p31 comet protein (Habu et al 2002;Teichner et al 2011;Westhorpe et al 2011), which has recently been implicated in targeting an AAA ATPase to the MCC to initiate its disassembly (Eytan et al 2014;Wang et al 2014).…”
Section: The Biochemistry Of Mitosismentioning
confidence: 99%